Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Publisher: African Development Bank Group 978-9973-9854-5-3 (electronic)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Mozambique: Analytical Report on Decentralisation - Salimo, Padil (Asociação Nacional de Municipios de Mozambique - ANAMM, EU and UCLG Africa, 2020)
The United Cities and Local Governments of Africa (UCLGA) commissioned this report in coordination with the National Association of Municipalities of Mozambique (ANAMM) to analyse the political economy of decentralisation of Mozambique. The report provides information in support of the ANAMM discussion and dialogue toward the new European Union (EU) programming process of cooperation with local authorities (LAs) for the 2021-2027 period. This report was developed in line with another called “Compendium of References” which is also part of the preparation for the EU programming process of cooperation with the Las. The analytical report on political economy pretends to explore the extent to which the central government embraced the conceptualisation of territorial development, the level of commitment of central government in recognizing the role of local authorities in the territorialisation of the national development agenda, and the opportunities and constraints created by the decentralisation system for the empowerment of local authorities as developmental actors. The political economy analysis catches the key aspects of how political and economic power influences the way how decentralisation is implemented and contested, the incentives behind the political actors and interests groups and how they impact the decentralisation reforms outcomes. The report serves as a background document to a seminar of the members of the ANAMM, which is part of a process of building consensus over the key priority action to include in the municipalities’, or interchangeably called in the report also as local authorities, roadmap for dialogue with the central government and the EU Delegation in Maputo, Mozambique. The expected result involves the following: (i) An analysis of the political economy of decentralisation, the feasibility of the new local authorities (LAs) driven political agenda and the opportunities and constraints created by the decentralisation reforms; (ii) An overview of the state of art regarding the territorialising of national policies and global agendas including SDGs, in terms of both policies and programs adopted in the framework of the national development plan; (iii) A SWOT quick analysis of the ANAMM; and (iv) The state of the art concerning the territorialisation of national policies and global programs, including Sustainable Development Goals (SDGs), both at the level of policies and programs implemented within the framework of the National Development Plan.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Centro de Integridade Pública (Public Integrity Centre), 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, João (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
ISBN: 9782490093182 OCLC: 1199064112
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
OCLC: 1164631287
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Publisher: Routledge
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Education Service Delivery in Mozambique: A Second Round of the Service Delivery Indicators Survey - Bassi, Marina; Medina, Octavio; Nhampossa, Lúcia (World Bank, 2018)
This report presents the findings of the second round of the Service Delivery Indicators Survey (SDI) in Mozambique. The SDI analyses the performance of the education sector by assessing the quality of service delivery at the school level. SDI has been implemented in nine countries in Africa, including Mozambique in 2014.5 The study includes a set of indicators that measures teachers and principals’ ability and effort, as well as the availability of key inputs and resources that contribute to the functioning of a school. These metrics enable education authorities and schools to identify gaps and track progress over time (and across countries). The analysis is centered around three main questions: what do providers know? (teacher ability), what do providers do? (teacher effort), and what do providers have to work with? (input availability).
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; education / educação

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (World Bank, Washington, DC, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (Chr. Michelsen Institute, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Mozambique: Report 8/2016 Country Evaluation Brief - Tvedten, Inge; Orre, Aslak (Norwegian Agency for Development Cooperation (Norad), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Government Decentralization Program in Indonesia - Nasution, Anwar (Asian Development Bank Institute, 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

JICA in Mozambique Brochure - Japan International Cooperation Agency (JICA) (2016)
1. What is JICA? Since joining the Colombo plan in 1954, Japan has been providing financial and technical assistance to developing countries through ODA (Official Development Assistance). JICA is the "one stop shop of Japan's bilateral ODA'', providing Technical Cooperation, ODA Loans (Concessional Loans) and Grant Aid. JICA has a network of more than 90 overseas offices. In Mozambique, JICA opened office in 2003. 3. Priority Areas in Mozambique: 1) Activation of Regional and Local Economies 2) Environment and Climate Change Action 3) Human Development & Capacity Building
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Number: 2
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

An Analysis of Mozambique’s Political and Economic Networks - Chivangue, Andes; Cortez, Edson (CEsA - research center part of CSG/Research in Social Sciences and Management, 2015)
This paper analyses the social networks existing among politicians and economists in contemporary Mozambique, using the SNA-Social Networks Analysis method to identify the links between these individuals, to discern their relationships and to measure both the density and the centrality of the political-business network. Mozambique’s political and business elite is thus identified. A network sociogram is presented identifying the individual position in the network and the linkages among these individuals and several positional metrics of the individuals in the network are estimated, allowing identifying each individual and its influence in the network. As this network is resource accumulation driven, this exercise permits to identify the main political and economic individual active in Mozambique economy. President Guebuza define the major network centre and other individuals, Joaquim Chissano, the former president, and Graça Machel, the widow of another former president. Policy implications are derived and the links between them displayed, allowing for an accurate view of Mozambique’s political and business world.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Publisher: International Research Center for Energy and Economic Development (ICEED)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Number: 2
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

The Human Rights Impacts of Tree Plantations in Niassa Province, Mozambique - Seufert, Philip; Santos, Ricardo (FIAN International, 2012)
This study investigates the impairing of the rights of peasant communities through the establishment of tree plantations in Niassa province, Mozambique. More particularly, it looks at the impacts of the operations of Chikweti Forests of Niassa on the local population in the districts of Lago, Lichinga and Sanga. In order to do so, it presents an introductory chapter on the general context of Mozambique and the legal framework. This legal framework will serve as a basis on the analysis of the findings of this study using a human rights approach. It contains an overview of national and international provisions relevant to the case. This includes Mozambican national legislation and policies, as well as standards under international human rights law. Regarding the latter, it puts a particular focus on extraterritorial obligations (ETOs), recently clarified by the Maastricht Principles on Extraterritorial Obligations, and includes provisions related to access to land and related resources, as contained in the Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; rural development / desenvolvimento rural

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

Ten years of single window implementation: lessons learned for the future - Koh, Jonathan (Global Trade Facilitation Conference 2011, 2011)
This paper examines the Single Window concept and its developments in practice over the last 10 years and provides an analysis of its development over time. An overview of the emerging information technology that would impact its future development is also presented. The paper also examines regional trends in Single Window implementation, based on a survey of tenders documents issued by various countries in the recent years. Finally, it offers an outlook on its future development and provides a number of recommendations.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Local economic governance: a survey of business operators in 245 districts/municipalities in Indonesia, 2011 - The Asia Foundation; Regional Autonomy Watch (The Asia Foundation, 2011)
Decentralization has been underway in Indonesia for more than ten years, but recently many have challenged the how effectively decentralization – and even democratization – is being implemented. Deterioration in the quality of public services, the many corruption cases involving local governments, and low economic growth rates in some regions have prompted discourse about whether the country is making a reversal away from decentralization and democratization. We recognize that the move toward regional autonomy has not been without its faults. Nevertheless, a choice was made to strengthen democracy and move towards local autonomy based on the problems created by the centralistic, authoritarian system of the previous regime. Yet it is unfair to judge regional autonomy a failure after it has been implemented for such a short time, and under a somewhat inconsistent policy framework. Since 2001, the Regional Autonomy Watch (KPPOD) and The Asia Foundation have aimed to present a clear picture of the quality of regional economic governance from the perspective of business owners. Our studies provide input to government at the central, provincial and regional/municipal levels, as well as information to other stakeholders regarding efforts that can be undertaken to promote improve economic growth under regional autonomy. This year’s study finds significant variation among regions in the quality of economic governance. This indicates that despite many limitations, some regions have used the opportunities provided by autonomy to foster good governance while others have not. It is hoped that this present study, and the awards presented to regencies and municipalities with the best performance, will promote a healthy competition among regional leaders. It is also envisioned that local governments whose performance is still low can learn from their neighbors who are doing better, and be inspired to improve. We recognize that improving economic governance requires a strong commitment and hard work, not only from the heads of regions but from all ranks of government officials, politicians, business owners and other stakeholders. This study can help set priorities for reform of local economic governance, identifying areas for immediate improvement that are relatively easy to achieve but have the potential of significant impact. Other aspects may need more time for improvement.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; M - survey / inquérito; Northern PEA; decentralization / descentralização

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Final Report 1 of 3 Summary - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part I-II - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-V - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors)
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Small and Medium Enterprises (smes) Access to Finance in Selected East Asian Economies - Harvie, Charles; Oum, Sothea; Narjoko, Dionisius A (ERIA - Economic Research Institute for ASEAN and East Asia, 2010)
Findings from ERIA’s SME research project in FY 2009 confirms that access to finance is amongst the most critical factors determining the competitive readiness of regional SMEs and their ability to fully exploit and participate in the global economy and business opportunities from regional economic integration and, in particular, participation in regional production networks. Well recognized in the literature, access to funding is the lifeblood of any enterprise, enabling it to grow, and to generate more output and employment. There is considerable evidence to support the contention that SMEs, in particular, face a number of obstacles and problems in accessing finance, mainly related to their limited resources and perceived risk by lenders. This is particularly problematic and worrisome for policy makers, given that SMEs and entrepreneurship are widely recognized as being the key sources of dynamism, innovation, and flexibility in advanced industrialized, emerging market and developing economies, and are major net job creators in these economies. Without access to finance, SMEs are unable to invest, impairing their capacity to: improve productivity; raise competitiveness; promote innovation; generate employment; and contribute to economic growth and development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; ⛔ No DOI found

The Expansion of Tree Monocultures in Mozambique. Impacts on Local Peasant Communities in the Province of Niassa - Overbeek, Winfridus (Movimento Mundial pelas Florestas Tropicais, 2010)
This publication is the result of a visit to Mozambique in November 2009 by two activists involved in the struggle against tree monocultures in the Brazilian state of Espírito Santo. This visit was made possible by the World Rainforest Movement (WRM) with the goal of exchanging experiences about large-scale tree monocultures. With more than 40 years of dealing with monoculture plantations and expansion, Brazil has a lot of experience in this area. At the same time, affected communities and supporting organizations in the country have led several struggles and acts of resistance and formed alliances, which nearly ten years ago resulted in the foundation of the Alert against the Green Desert Network (Rede Alerta contra o Deserto Verde). In the past few years, WRM has been made aware of the fact that more and more tree monocultures are being planted in Mozambique. Since Brazil and Mozambique have in common Portuguese as their official language, the idea arose to promote the exchange between the two countries so as to: − exchange experiences with the affected communities about the impacts; − better understand the current situation of the introduction and expansion of tree monocultures in Mozambique; and, − identify organizations involved or interested in the subject. This visit would not have been possible without the invaluable help of our friends at UNAC (União Nacional de Camponeses - National Peasant Union) in Mozambique, and UCA (União dos Camponeses e Associações de Lichinga - Union of Peasant and Associations of Lichinga), who volunteered to receive and accompany the Brazilian delegation and organized the visits to the communities. We also want to thank Via Campesina Brasil for their support in this initiative.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural

Gender and poverty in Mozambique - Tvedten, Inge (CMI, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
ISBN 978-91-85735-17-4
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

The politics of gradualismo: popular participation and decentralised governance in Mozambique - Buur, Lars (Rethinking Popular Representation., 2009)
The question of how to proceed with democratic decentralisation has been of political concern in Mozambique over the past decade. In accordance with post-war constitutional commitments to démocratisation after the country’s post-independence flirtation with socialism and a high degree of centralism, the process of decentralisation has taken two forms. First, a system of locally elected governments in the form of municipalities (municipios) for the urban and semi-urban areas was approved in 1997 to cover the devolution of direct although limited powers and functions to autonomous elected bodies. The Municipal Law (2/1997) made provision for locally elected municipalities (autarquias locais) in 33 urban or peri-urban settings.1 Second, for the rest of the population (roughly .70 percent) and the local state administration, the process of decentralisation has taken the general form of de-concentration and a transfer of responsibility to lower level bodies within the state sector combined with different forms of participatory mechanisms for representation and consultation. These participatory mechanisms are grounded in community- based organisations claiming representative status on the basis of identity, interest, community, and similar factors.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; governance / governação

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Publisher: Falmer : University of Sussex
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

Higher fuel and food prices: impacts and responses for Mozambique - Arndt, Channing; Maximiano, Nelson; Thurlow, James T.; Nucifora, Antonio M. D. (Agricultural Economics, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer-term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (World Bank, 2008)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people— sectors that are more export oriented, labor intensive, and knowledge driven. These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past. This report is different. Its objective is to provide a better understanding of barriers to investment and doing business that may be common to all investors and those that affect women entrepreneurs disproportionately. The report examines newly available data from more than 4,800 surveyed firms in the formal sector in eight Middle East and North African countries (the Arab Republic of Egypt, Jordan, Lebanon, Morocco, Saudi Arabia, the Syrian Arab Republic, Gaza and the West Bank, and the Republic of Yemen). These surveys detail firm characteristics and the responses of male- and female- owned firms to questions about perceived barriers along 18 categories of the investment climate. The purpose of the report is threefold: • to provide an overview of the characteristics of female- owned firms in the region; • to analyze gender- specific barriers that exist across the region or within countries; and • to identify other factors outside the business environment that might affect women’s entrepreneurship. The report finishes with policy recommendations on how to reduce the identified barriers and create a level playing field for women entrepreneurs. The report acknowledges limitations resulting from the availability and depth of data. It does not attempt to answer every question about women’s entrepreneurship in MENA. Indeed, it may raise more questions than it answers. The hope is to spur greater interest in the topic among researchers and policy makers.
Issue: 44824
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Adverse incorporation, social exclusion and chronic poverty - Hickey, Samuel; Andries du Toit (Institute for Development Policy and Management, School of Environment and Development, University of Manchester, 2007)
There are a number of compelling reasons to focus on the ways in which the processes and relations of adverse incorporation and social exclusion (AISE) underpin chronic poverty. In particular, AISE research draws attention to the causal processes that lead poverty to persist, and to the politics and political economy of these processes and associated relationships over time. Specific dimensions of AISE are explored in relation to chronic poverty – namely political, economic, socio-cultural and spatial – and are found to relate closely to long-term historical processes, particularly concerning the nature and forms of capitalism, different stages and types of state formation, and institutionalised patterns of social norms and attitudes. However, it is also stressed that much of the promise of AISE research lies in its capacity to cross analytical boundaries and capture the multi-dimensional and interlocking character of long-term deprivation. This analysis suggests a number of fruitful areas for research, most of which are currently under-explored in poverty research. In methodological terms, there are benefits to adopting integrated qualitative-quantitative approaches when investigating AISE, although it is argued that (a) the relational nature of AISE and the limitations of quantitative data may dictate that qualitative work should take priority here and (b) that more historical and theoretically oriented forms of research are particularly appropriate in studying AISE. To think about challenging AISE involves shifting the frame from policy to politics and from specific anti-poverty interventions to longer-term development strategies, particularly in terms of industrialisation and labour market restructuring, moves towards developmental states and supporting shifts from clientelism to citizenship. However, a range of more immediate development policy interventions may also be able to make headway in challenging the forms of AISE that perpetuate poverty.
OCLC: 317916213
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Palgrave Macmillan, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

Business licensing and one stop shops in Indonesia - Steer, Liesbet (The Asia Foundation, 2006)
In 2001, Indonesia embarked on a decentralization process that has had a dramatic impact on the local political landscape, especially in relation to taxation and administrative processes. Rules and procedures that govern licensing, registration, some taxes and user charges have largely been devolved to local governments. A significant number of new licenses and charges have been created at the local level, and most licenses are issued through a complicated system of procedures and agencies. Licensing has become one of the most important barriers to business formalization and growth in Indonesia. The local licensing framework in Indonesia has three key problems, raising transactions costs and inefficiencies. Licensing reform through One Stop Shops (OSS). The Asia Foundation OSS technical assistance program. The methodology has proven to be highly effective.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Number: 2
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água; higiene e saneamento; health / saúde; private sector / setor privado

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Number: 71 Publisher: Southeast Asia Program Publications at Cornell University
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

'Dhlakama É Maningue Nice!': An Atypical Former Guerrilla in the Mozambican Electoral Campaign - Cahen, M. (Transformation, 1998)
Despite significant problems with urban criminal gangs and highway robbers, Mozambique is a country at peace since 4 October, 1992. Under the auspices of the Italian religious congregation of Santo Egidio,4 Joaquim Alberto Chissano, president of the Republic and of the Frente de libertagao de Mozambique (FRELIMO), once the 'Marxist-Leninist' single-party of the country, and Afonso Dhlakama, president of the Resistencia national de Mogambique (RENAMO), the former guerrilla group and longtime recipient of aid from South Africa, signed the 'General Peace Accord' on that date. This agreement has never seriously been called into question. During the first 15 days following the accord there were a number of incidents. For example, it contained provisions for maintaining each party's administration in their part of the country, but did not specify the zones belonging to one party or the other. As a result, a number of RENAMO regional commanders sought to occupy areas that they had not previously controlled, the largest one being Angoche in Zambezia. It appears that they had told Afonso Dhlakama that they already held these areas, and following the peace accords, they urgently sought to gain real possession of the territory in question.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict / conflito; ⛔ No DOI found

Women in Mozambique: Gender Struggle and Gender Politics - Arnfred, Signe (Review of African Political Economy, 1988)
The liberation of women is a fundamental necessity for the revolution, a guarantee of its continuity and a condition for its success (Machel, 1973). In his opening address to the first conference of the Mozambique Women's Organisation (OMM) in 1973, Samora Machel, President of Frelimo, affirmed that women's emancipation was an integral aspect of revolutionary struggle. In 1973 Frelimo was still a liberation front engaged in armed struggle against colonial rule. The northern part of Mozambique was a battle ground and the first OMM conference had to be held in the Frelimo camp at Tunduru in southern Tanzania. In the OMM's present national. secretariat in Maputo, a photograph of the participants of this first conference can be seen. Peasant women and women guerilla's are lined up outside the meeting hut, amongst them Samora Machel in battledress. The non-hierarchical atmosphere depicted in this photograph is in marked contrast to the more formal arrangements on similar later occasions. The participation of women in the war was massive. In 1967, at the request of women themselves, a women's detachment of the guerilla army - Destacamento Feminino - had been formed. Part of its task was to inform and mobilise the peasant population. To support this work, a broader non-military organisation of women was needed. This was the origin of the foundation of the OMM in 1973.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; gender / género

Ethnicity, Politics, and History in Mozambique - Alpers, Edward A. (Indiana University Press, 1974)
Conclusion Of course, the political disgrace of Joana Simiao does not by itself solve the problem of Makua-Lomwe separatism, any more than the collapse of the Movement for a Free Mozambique has solved the larger problems of national reconstruction in Mozambique. But by now it should be clear to all that the only political movement qualified to achieve that goal is FRELIMO, who demonstrably are working for the interests of all Mozambicans and who enjoy the support of Mozambicans of all races, religions, and ethnic backgrounds, including both Makua-Lomwe and Maconde. During its decade of armed struggle FRELIMO has successfully defended its just cause against attack from without and dissension from within. In the process it has painstakingly built a truly national liberation movement. The lessons learned in that crucible, which se suddenly belongs to the past, must now be applied to the future
Publisher: Indiana University Press
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; politics / política; ⛔ No DOI found

Development for Whom?: From the Case of the ProSAVANA Project in Mozambique – Master of Development Practice - Go Suzui
ProSAVANA project in Mozambique There are tremendous numbers of development projects all over the world. Mozambique is one of the least developed countries. A serious issue in Mozambique is food security. Even though 80 percent of the labor force in Mozambique engages in agriculture (USAID 2017), Mozambique’s farmland is tropical savanna that features very poor soil quality, and Mozambique does not have technologies to overcome this issue. As related to a food security issue, more than two out of five children under five years old are malnourished in Mozambique (UNICEF Mozambique 2017). The government of Mozambique decided to transform the current agriculture system and ensure food security. ProSAVANA is a triangular cooperation program among Mozambique, Brazil and Japan since 2009. The Japan International Cooperation Agency, the Japanese Ministry of Foreign Affairs and the Brazilian Cooperation Agency have participated in this project. The main purpose is to “improve the livelihood of inhabitants of the Nacala Corridor through inclusive and sustainable agricultural and regional development” and to “create employment through agricultural investment and establishment of a supply chain,” (ProSAVANA 2016). It seems that ProSAVANA has positive impacts on agriculture and on the total GDP of Mozambique and can improve childhood nutrition.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental

Islamic Radicalization in Northern Mozambique: The Case of Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE))
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui. —– This research report is a first attempt to address the phenomenon in order to understand the complexity of the dynamics not only in the origin of the Al-Shabaab group but also in the structure of the conflict and violence in Cabo Delgado. Almost two years after the first attack on Mocímboa da Praia (5 October 2017), the phenomenon has been the subject of multiple interpretations, from the (at least public) Mozambican government’s preferred thesis of a conspiracy driven by external forces opposed to Mozambique’s development, through the land conflict against the backdrop of the area’s natural resources thesis, to the sect (Morier-Genoud, 2019) and jihadism theses, in the context of the growing dynamics of violent extremism in the countries of the region i.e. Tanzania, Kenya and the Great Lakes region. While highlighting this last thesis (jihadism), our exploratory research has shown that the phenomenon is complex and requires profound multidisciplinary research that takes into account a multiplicity of historical, social, political, economic and religious factors. This is why, rather than draw conclusions, this report ends with a series of questions: • Why is Mocímboa da Praia the epicentre of the phenomenon? • How does the Mozambican state deal with the proliferation of religious institutions in the country? • What are the implications of the Islamic radicalization phenomenon for investments in the country’s northern region? To what extent can these investments heighten or reduce local cleavages and contribute to Islamic radicalization phenomenon? • To what extent does the Islamic radicalization phenomenon affect current efforts to stabilize the country politically and economically? • To what extent can regional dynamics (Tanzania, Kenya, Great Lakes region) influence the evolution of the phenomenon in Mozambique? • What kind of policies (including security) does the country need to address the phenomenon? • What lessons does the phenomenon bring to the state-building process in Mozambique? These questions feed into the ongoing research program at the Institute for Social and Economic Studies (IESE) since early 2019, involving researchers from IESE and other research centres, entitled “State, Violence and Development Challenges in Cabo Delgado”.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Subnational HDI - Global Data Lab - Iñaki Permanyer; Jeroen Smits (Global Data Lab - Nijmegen Center for Economics (NiCE), Institute for Management Research, Radboud University)
Subnational Human Development Index - Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde

Mozambique HDI Data - UNDP
Access and explore human development data for 191 countries and territories worldwide. Select Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia